2002
DOI: 10.1007/s00213-002-1233-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of ethanol on extracellular dopamine in mesolimbic striatum of awake rhesus monkeys: comparison with cocaine across individuals

Abstract: These results provide support for the ability of ethanol to elevate extracellular dopamine in the mesolimbic striatum, though with a modest effect size and variability among individuals. Further, they suggest that some common mechanism influences the effects of ethanol and cocaine on dopaminergic output despite seemingly unrelated pharmacological mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 73 publications
1
12
1
Order By: Relevance
“…Our present work also parallels an emerging view that the NAc DA release observed following investigator-administered alcohol was provoked by novelty, unexpectedness, and/or aversiveness of the administration (Bradberry, 2002; Gonzales et al, 2004; Heidbreder and De Witte, 1993; Imperato and Di Chiara, 1986; Joseph et al, 2003; Marinelli et al, 2003; Philpot and Kirstein, 1998; Yan, 1999; Yim et al, 1998, 2000; Yoshimoto et al, 1992). Although several studies have documented increases in NAc [DA] during oral self-administration of alcohol (Doyon et al, 2005; Gonzales and Weiss, 1998; Melendez et al, 2002; Weiss et al, 1992, 1993, 1996), Doyon and colleagues (2003, 2005) showed that increases in NAc [DA] were dissociated from changes in brain ethanol concentration: NAc DA levels peaked 5 minutes after the onset of oral alcohol self-administration, then gradually tapered off over the next 30 minutes as the animals continued to drink alcohol and brain ethanol levels continued to rise.…”
Section: Discussionsupporting
confidence: 84%
“…Our present work also parallels an emerging view that the NAc DA release observed following investigator-administered alcohol was provoked by novelty, unexpectedness, and/or aversiveness of the administration (Bradberry, 2002; Gonzales et al, 2004; Heidbreder and De Witte, 1993; Imperato and Di Chiara, 1986; Joseph et al, 2003; Marinelli et al, 2003; Philpot and Kirstein, 1998; Yan, 1999; Yim et al, 1998, 2000; Yoshimoto et al, 1992). Although several studies have documented increases in NAc [DA] during oral self-administration of alcohol (Doyon et al, 2005; Gonzales and Weiss, 1998; Melendez et al, 2002; Weiss et al, 1992, 1993, 1996), Doyon and colleagues (2003, 2005) showed that increases in NAc [DA] were dissociated from changes in brain ethanol concentration: NAc DA levels peaked 5 minutes after the onset of oral alcohol self-administration, then gradually tapered off over the next 30 minutes as the animals continued to drink alcohol and brain ethanol levels continued to rise.…”
Section: Discussionsupporting
confidence: 84%
“…Across species, EtOH shares with cocaine the ability to acutely increase brain DA concentrations (e.g., Bradberry, 2002; Di Chiara and Imperato, 1988; Yoder et al, 2009), which has long been identified as the primary mechanism of cocaine’s abuse-related effects (e.g., Koob and Volkow, 2010; Pierce and Kumaresan, 2006). Moreover, brain-imaging studies in both cocaine and alcohol abusers have indicated that chronic consumption results in decreased brain DA D2-like receptors (for review see Cosgrove 2010) and a hypofunctional state of DA neurotransmission (e.g., Henry et al, 2009; Karkhanis et al, 2015; Parsons et al, 1991; Weiss et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of cocaine’s abuse-related effects by EtOH would be expected based on its ability to increase striatal dopamine (DA) concentrations (e.g., Bradberry, 2002; Di Chiara and Imperato, 1988; Yoder et al, 2009). Moreover, similar alterations in brain DA systems—particularly D2 receptors—have been observed in alcoholics and cocaine abusers (e.g., Cosgrove, 2010; Volkow et al, 1996,1999, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis studies in the behaving animal demonstrated that response-independent, systemic administration of cocaine, amphetamine, heroin, cannabinoids, nicotine, and ethanol increase dopamine levels in the NAcc (DiChiara 1986; Imperato and Di Chiara 1986; Imperato et al 1986; Di Chiara and Imperato 1988; Kalivas and Duffy 1990; Kuczesnki et al 1991; Yoshimoto et al 1992; Pontieri et al 1996; Tanda et al 1997). The dose of the drug administered and the concentration of striatal dopamine following drug administration are positively correlated, as demonstrated for cocaine and ethanol (Nicolaysen et al 1988; Bradberry 2002). Similar to response-independent drug administration, self-administered drugs of abuse, including cocaine, amphetamine, heroin and ethanol, induce increases in concentrations of dopamine in the NAcc (Hurd et al 1989, 1990; Pettit and Justice 1989, 1991; Weiss et al 1992, 1993; Di Ciano et al 1995; Wise et al 1995a, b).…”
Section: Effects Of Drugs Of Abuse On Extracellular Dopamine Concenmentioning
confidence: 91%